Yenching University and Modern Women's Higher Education in China (1920–1928) - WANG, Cuiyan (Journal of Research for Christianity in China (JRCC), 2025)
This paper primarily draws upon archival materials from Yenching University, supplemented by relevant memoirs from its alumni, to examine the educational landscape of Yenching University's women's college and its significance for modern women's higher education. Since the independence of the women's college, which existed as the Women's Department of Yenching University after 1928, had largely disappeared, its form of women's education became largely similar to other forms of coeducational women's higher education in China. Therefore, this study focuses solely on the period when it functioned as the Yenching University Women's College (1920–1928).